National history and migrant history after the transnational turn: the French in Australia and the articulation of Frenchness - Alexis BERGANTZ (E-REA)
This article considers the advancements made in Australian historical scholarship since the transnational turn and how these can now be applied to the writing of national histories. In particular, by considering the case of ‘the French presence’ in Australia, it explores how transnational insights can help bridge the historiographical divide between ‘ethnic’ or ‘contribution’ history and mainstream Australian history through the use of cultural theory.